Transtorno do espectro autista: a linguagem como instrumento de inclusão social e educacional - Costa, Aguida Luiza Dias da (2023)
This work addresses the role of language as a tool for social and educational inclusion for individuals with Autism Spectrum Disorder (ASD). The key question of this study is: "How does language act as a tool for social and educational inclusion for autistic children in the learning process?" The central objective of this research is to analyze the contribution of language both to the inclusion and exclusion of individuals with ASD in the educational sphere and in society at large. We hypothesize that language plays a crucial role in inclusion when professionals involved have knowledge about the autistic spectrum and its communication forms. However, we acknowledge that language can also be excluding when those who interact with autistic individuals do not understand the complexity of their communication. The methodology used in this study is documentary in nature, with an emphasis on the use of psychopedagogical records of autistic children from the Mundo Autista School Clinic in Araguaína, Tocantins. The analysis of the results revealed that all the patients mentioned in this study have been receiving treatment from the researcher for a period of approximately 1 to 2 years. During the sessions, a variety of communication strategies were identified to meet the specific needs of each child. In addition to verbal language, non-verbal language and communicative adaptations played an essential role. The construction of a trustful environment between the child and the professionals emerged as a determining factor. Through this relationship, children feel secure to express themselves and actively participate in activities. Language, in this context, served as a bridge to establish this emotional and communicative connection, allowing children to engage more fully in their learning. The results also demonstrated that the communication strategies adopted in the clinic contributed to the progressive development of linguistic and communicative skills in children. Through individualized and sensitive approaches, children showed progress in verbal expression, understanding commands, and interaction with others. Thus, the analysis of the results confirmed the hypothesis that language plays a fundamental role in the social and educational inclusion of autistic children. Through appropriate communication strategies and the construction of a trustful environment, language becomes an effective tool to promote active participation, cognitive and emotional development, and the integration of these children into educational and social activities.